Encyclopedia of Mathematics Education (Springer Netherlands, 2018)
The Encyclopedia is intended to be a comprehensive reference text, covering every topic in the field with entries ranging from short descriptions to much longer pieces where the topic warrants more elaboration. The entries will provide access to theories and to research in the area and will refer to some of the leading publications for further reading. Links will also be made to particular texts in Springer journals and e-books through SpringerReference.com which will be launched in Summer 2011 to accompany SpringerLink.com. The Encyclopedia will be aimed at graduate students, researchers, curriculum developers, policy makers, and others with interests in the field of mathematics education. It is planned to be two volumes in its hard copy form but the text will subsequently be up-dated and developed on-line in a way that retains the integrity of the ideas, the responsibility for which will be in the hands of the Editor-in-Chief and the Editorial Board.